INOVASI PEDAGOGIK DAN TEKNOLOGI PENDIDIKAN: MENINGKATKAN KUALITAS PEMBELAJARAN DI ERA DIGITAL - Muhadi, Andi; Robandi, Babang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand the implementation of pedagogy from the perspectives of teachers and students and its impact on learning quality. Using a qualitative approach with a descriptive method, the research was conducted in several secondary schools selected based on student diversity and the adoption of pedagogical innovations by teachers. Data were collected through in-depth interviews, classroom observations, and documentation, then analyzed using a thematic analysis approach. The findings reveal that student-centered learning strategies enhance student motivation and engagement, while the use of educational technology positively impacts the learning process. However, challenges such as limited facilities and the need for individual student guidance remain significant. This study highlights the importance of pedagogical innovations relevant to student needs in the digital era to improve education quality.